THE AUTOMATIC DOORS INTEGRATED ABSENCE AND USER ACCESS USING FINGERPRINT - Rizqia Cahyaningtiyas; Efy Yosrita; Rakhmat Arianto (Jurnal Ilmiah FIFO, 2016)
This research aims to design Accompanied Door Access System Automation Absence and User Access Rights Using Integrated Fingerprint Database on Basic Computer Lab Informatics STT-PLN. What is meant by "Absent Automation and User Access Rights" among other computerized attendance automatically using fingerprint and right into a room on a predetermined schedule of lectures on computer lab space. System design method used is the method of evolutionary prototype, using MySQL database and coding using Visual C # .NET. These results indicate that the Door Access System Automation Accompanied Absence and User Access Rights Using Integrated Fingerprint Database can help assistants in attendance processing, computer lab room becomes more secure and computerized